2021
DOI: 10.1155/2021/6684568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Supplementation of L‐Arginine on Physical Fitness in Water Polo Players

Abstract: Background. Ergogenic nutritional supplementation is sought by professional athletes for improving physical performance; nevertheless, scientific evidence to support the chronic use of L-Arginine among water polo players is missing. Methods. Seventeen male professional water polo players were randomly assigned to assume 5 grams per day of L-Arginine ( n = 9 ) or placebo ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Thus, in order to assess the role of L-arginine supplementation in the reduction of respiratory support, we performed a multivariate analysis which demonstrated that treatment with Larginine was the main determinant of this phenomenon, ruling out the possibility that it could be merely due to the younger age of this group of patients. This conclusion is corroborated by the observation that L-arginine supplementation was the main determinant in the reduction of in-hospital stay duration; the in-hospital stay median (IQR 25 th ,75 th percentile) number of days was 46 (45,46) in the placebo group vs 25 (21,26) in the L-arginine group (p < 0.0001, Mann-Whitney); this finding was also confirmed after adjustment for potential confounders including age.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Thus, in order to assess the role of L-arginine supplementation in the reduction of respiratory support, we performed a multivariate analysis which demonstrated that treatment with Larginine was the main determinant of this phenomenon, ruling out the possibility that it could be merely due to the younger age of this group of patients. This conclusion is corroborated by the observation that L-arginine supplementation was the main determinant in the reduction of in-hospital stay duration; the in-hospital stay median (IQR 25 th ,75 th percentile) number of days was 46 (45,46) in the placebo group vs 25 (21,26) in the L-arginine group (p < 0.0001, Mann-Whitney); this finding was also confirmed after adjustment for potential confounders including age.…”
Section: Discussionsupporting
confidence: 56%
“…The formulation of Bioarginina Ò used in this study consists of oral vials containing 1.66 g of L-arginine, whose taste is fully buffered by the presence of sucrose and by an acidity regulator (anhydrous citric acid); therefore, there were no differences in appearance, smell, or taste between treatment and placebo. The dose was chosen based on a previous study proving that such a regimen was safe and significantly effective in ameliorating the oxidative metabolism of professional water polo players [21]. Respiratory support was defined as follows (from the more to the less intense one): NIV: non-invasive ventilation; CPAP: continuous positive airway pressure; HFNC: highflow nasal cannula; LTOT: Long-term oxygen therapy [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low plasma concentration of L-arginine results in impaired L-arginine-NO signaling and may promote endothelial dysfunction [32]. Also, L-arginine has been effective in decreasing oxidative metabolism in water polo players [33]. Another important carbohydrate-like substance, vitamin C, has an antioxidant effect and protects vascular endothelial function as well.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were randomly assigned to the L-Arginine (Bioarginina ® , 1.66 g, twice a day) or placebo ( n = 37) parallel groups and followed-up for 4-weeks. The dose of L-Arginine was based on previously published clinical trials ( 33 , 34 ).…”
Section: Methodsmentioning
confidence: 99%